Conceptual Design of a Coffee Shop Sales Information System Using the Unified Modeling Language (UML) Approach - Kurniati, Nia; Selamat, Rachmat (Jurnal Impresi Indonesia, 2026)
The increasing volume of transactions in coffee shop businesses requires a structured and informative sales data management system. Sales data that are not managed through a well-designed system may lead to recording errors, delays in reporting, and limited information to support managerial decision-making. This study aims to conceptually design a coffee shop sales information system by utilizing sales transaction data as the basis for system requirements analysis. The research method employed is systems analysis and design using the Unified Modeling Language (UML) approach. The design process includes actor identification, functional requirements analysis, use case modeling and scenarios, activity diagrams, sequence diagrams, and class diagrams, complemented by conceptual user interface (UI/UX) design and data normalization. The results of this study produce a conceptual design of a sales information system that can serve as a blueprint for future system development